PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN PADA POM COFFEE BATAM - Pramana, Ryan; Nainggolan, Nora Pitri (SCIENTIA JOURNAL, 2021)
To maintain customer satisfaction, companies need to improve human resourcemanagement who are the backbone of the company. Service_quality_and_product_qualitygreatly_affect_customer_satisfaction. This study aims to examine the effect of servicequality and product quality on customer satisfaction at Pom Coffee Batam. The design ofthis research is quantitative research. The behavioral technique used is the Slowin formulaby interviewing 100 people. The data was collected using a questionnaire using a Likertscale measurement. The data analysis method used in this research is descriptiveanalysis, validity test, reliability test, multiple linear regression analysis, analysis of thecoefficient of determination (R2), t test, and F test. Then the data is processed using SPSSversion 24 software. positive and significant on customer satisfaction. The total t for theQoS variable is 3,416> 1,984 (Table t). Product quality has a positive and significant effecton customer satisfaction, where the total calculation of the product quality variable is4.192> 1.984 (Table t)._The_F_test results show that service quality and product qualitytogether have a_positive and significant effect on customer satisfaction, because the testresults obtained a value of 41.434 <ftable 3.09 and a sig value of 0.000 <0.05.